UPAYA PENINGKATAN KINERJA PEGAWAI PADA DINAS PENGELOLAAN KEUANGAN DAN ASET KABUPATEN ROKAN HULU - -, Helvanora (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
The purpose of this research is to findout the efforts to increasing the workperformance in the Dinas Pengelolaan danAset Kabupaten Rokan Hulu. Theinformants of this research are Leader andSecretary Dinas Pengelolaan dan AsetKabupaten Rokan Hulu.This research isKualitatif research, where is we get the datafrom the explanation of arranged thesentences as systematic and than we get theconclusion of the research.The efforts to increasing the workperformance DPKA are:1. Given the compensation for every worker2. Make working environment conducive.3. Make promotion wisdom.4. Carry out education and exerciseaccording to needed.5. Given the motivation6. Increase the discipline based onregulation.